Financial literacy, present bias and alternative mortgage products - John Gathergood; Jörg Weber (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2015)
Policymakers have expressed concern that some mortgage holders do not understand or correctly choose their mortgage products, especially alternative mortgage products (AMPs) with back-loaded payments. Using a specially design question module in a UK survey, we investigate the impact of consumer financial sophistication on the decision to choose an AMP over a standard repayment mortgage. We show poor financial literacy and present bias raise the likelihood of choosing an AMP. Financially literate individuals are also more likely to choose an adjustable rate mortgage, suggesting they avoid paying the term premium of a fixed rate mortgage.
Keywords: D10; D12; G21; 330; mortgage; financial literacy; present bias; alternative mortgage products